Phytochemical Pharmacological and Growth Promoting Study of Endophytic Fungi Rhizopus delemer Isolated from Abutilon indicum (L.) Sweet.: Pharmaceutical Science-Biotechnology - Durairaj, Deepalakshmi; Sebastin Raj, Joseph (International Journal of Life Science and Pharma Research, 2022)
Endophytic fungi have been perceived as a potential source of bioactive secondary metabolites. Whereas Rhizopus as the endophytic fungi were isolated from the medicinal plant Abutilon indicum (L) sweet under the family Malvaceae found in tropical areas. This work aims to isolate and identify the fungal endophyte Rhizopus sp. from the medicinal plant Abutilon indicum at the molecular level, and the second objective is to test the Plant Growth Promoting activity like Indole Acidic Acid A, Hydrogen cyanide, Phosphate solubility (PO4), Catalase test, and it is the proof for plant endophyte association, lastly to analyse the extract of Rhizopus in phytochemical and pharmacology activity using Gas chromatography and Mass spectrometry study. The isolated fungal plant growthpromoting activity like Indole acetic acid production, Phosphate solubility assay, HCN production and Catalase enzyme synthesis was tested. As compared to IAA, PO4 solubility assay, HCN and Catalase synthesis test culture gave positive results. It described endophytic fungal within-hosts that are actively responsible against pathogens and stress tolerance conditions. Isolated fungal culture was able to synthesize catalase enzymes and HCN compounds. Rhizopus can act as a Phyto stimulator, broad-spectrum antimicrobial agent, increased stress tolerance capacity and also can increase the water availability in the nutrition supply to the host plant. In the qualitative screening test, there are about 12 phytochemicals that showed positive results. It gives the effort of the plant to act as a defensive mechanism against pathogens. Based on morphological and phylogenetic analyses, fungal species were identified: as Rhizopus delemer UICC 26. Accession no: LC514308. It is an unfamiliar mutant strain. Further GC-MS analysis revealed that the Identification of 20 bioactive compounds in the ethanolic extract of fungus Rhizopus delemer was Butane, 1,1-diethoxy-2-methyl-. 3,3-diethoxy-2-butanone. identified. The identification of bioactive chemical compounds is based on a Database in the National Institute of Standard Technology. The compound’s retention time, peak area, molecular weight and molecular formula were matched with WILEY and NIST Library. It could be concluded that the isolated endophytic fungus Rhizopus delemer UICC 26 extract was prominent endophytic fungi in Abutilon indicum plant and also it enhances the plant growth-promoting activity. It was confirmed by the positive results of HCN and Catalase production test. In 12 different phytochemical compounds, and among 20 bioactive agent’s presence 9 shown our fungi has active form inside of plant part against the pathogen.